Political Instability and Birth Outcomes: Evidence from the 1981 Military Coup in Spain - Ainoa Aparicio Fenoll; Libertad Gonzalez (Institute of Labor Economics (IZA), 2020)
We study the effect of exposure to political instability in-utero on health at birth. We exploit the coup d'état that took place in Spain on February 23, 1981. Although short-lived and unsuccessful, the event generated stress and fear among the population, especially in areas that had suffered more repression during the Civil War and the recent dictatorship. We follow a difference-in-differences strategy and compare birth outcomes before and after the coup, in areas that were differentially "affected". We find that children who were in utero during the coup in more affected areas were born with significantly lower birth-weight (around 9 grams lighter), especially if they were exposed to the coup in the first or second trimester of pregnancy. We contribute to the literature on the effects of maternal stress by focusing on an acute (and relatively common) source of distress that is unlikely to have affected newborn health via other channels.
Keywords: I12; J13; 330; birth outcomes; birth weight; political instability; military coup